PENGARUH SKILL MATRIX DAN MOTIVASI KERJA TERHADAP KINERJA OPERASIONAL DI PT.XYZ - Ahmad Pauji; Farhan Alyudin; Aditia (Universitas Mahendradatta, 2025)
This study aims to analyze the effect of skill matrix and employee motivation onoperational performance at PT XYZ. Data was collected through a survey of companyemployees using a questionnaire. Data analysis was carried out using the StructuralEquation Modeling (SEM) method with SmartPLS software. The results showed that the skillmatrix and employee motivation significantly positively affect operational performance. Theskill matrix also contributes to increasing employee motivation indirectly, therebystrengthening overall operational performance. The implication of this study is theimportance of implementing skill matrix and increasing employee motivation in humanresource management strategies to achieve operational efficiency.